The Relationship of Diet And Obesity With The Incidence of Hypertension - Rondonuwu, Rolly H.S; Tauwa, Mohamad Reski; Damping, Hendrik Herman; Wenno, Stefanny; Watuseke, Rommy David (Jurnal Ilmiah Perawat Manado (Juiperdo), 2023)
Background: Hypertension is a major challenge for Indonesia, as the disease is common in communities across the country. This is due to the many factors that cause hypertension including genetics, age, gender, ethnicity, stress, obesity, salt intake, high cholesterol intake, preserved foods, mutton, coffee and smoking. Objective: This study is to review one article with another article about the Relationship between Diet and Obesity with Hypertension. This type of research uses Literature Review research. Methods: articles were collected from search results on three databases such as Proquest, Pubmed and Google Scholar. With the criteria of articles published in 2015-2020, the author gets 20 articles and only 8 articles are used that match the research topic with a sample of 2176 respondents. Results: research from these eight articles showed an association between diet and obesity with the incidence of hypertension despite different research methods. Conclusion: based on the results of research and discussion, it can be concluded that an unhealthy diet and obesity can cause hypertension.